1996
DOI: 10.1099/0022-1317-77-1-37
|View full text |Cite
|
Sign up to set email alerts
|

Gene organization in the UL region and inverted repeats of the canine herpesvirus genome

Abstract: Restriction mapping and the determination of scattered nucleotide sequences have permitted a description of the global structure and evolutionary affinities of the canine herpesvirus (CHV) genome. The global structure closely resembles that of the totally sequenced genomes of varicella-zoster virus and equine herpesvirus 1 (EHV-1) in having a 37 bp inverted repeat flanking a long unique region (UL) of approximately 100000bp, and a 10100-10 700 bp inverted repeat flanking a short unique region (Us) of roughly 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
24
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 78 publications
4
24
1
Order By: Relevance
“…Taxonomically, CaHV-1 appears to be a monotypic virus that is genetically similar to feline herpesvirus-1 (FHV-1), phocid herpesvirus-1 (PhHV-1) and equine herpesvirus-1 (EHV-1) and -4 (EHV-4) [12,13]. However, the host range of CaHV is restricted to dogs only [14].…”
Section: Introductionmentioning
confidence: 99%
“…Taxonomically, CaHV-1 appears to be a monotypic virus that is genetically similar to feline herpesvirus-1 (FHV-1), phocid herpesvirus-1 (PhHV-1) and equine herpesvirus-1 (EHV-1) and -4 (EHV-4) [12,13]. However, the host range of CaHV is restricted to dogs only [14].…”
Section: Introductionmentioning
confidence: 99%
“…Cloning and sequencing of CHV-1 a-TIF Remand et al [35] published restriction enzyme maps of CHV-1 genome and 396 bp of sequence for the CHV-1 a-TIF OPF. Their maps and sequence were used to locate a clone from our CHV-1 EcoRI library that contained the complete a-TIF ORF (clone pJT037).…”
Section: Resultsmentioning
confidence: 99%
“…The gene structure of CHV has yet to be determined, since no CHV strain has been completely sequenced and only a few genes have been identified [73,96,132]. Restriction mapping, southern blot hybridization and sequence analysis have shown that the overall structure of CHV resembles those of other alphaherpesviruses and that CHV is genetically related to feline herpesvirus (FHV-1), phocid herpesvirus 1 and to the equid herpesviruses 1 and 4 [103,130,138,169].…”
Section: Canine Herpesvirusmentioning
confidence: 99%